Up‐regulation of micro‐RNA765 in human failing hearts is associated with post‐transcriptional regulation of protein phosphatase inhibitor‐1 and depressed contractility. (15th July 2015) - Cai, Wen‐Feng; Liu, Guan‐Sheng; Lam, Chi Keung; Florea, Stela; Qian, Jiang; Zhao, Wen; Pritchard, Tracy; Haghighi, Kobra; Lebeche, Djamel; Lu, Long Jason; Deng, Jingyuan; Fan, Guo‐Chang; et al.
<x xml:space="preserve">Abstract</x> Aims Impaired sarcoplasmic reticulum (SR) Ca2+ cycling and depressed contractility, a hallmark of human and experimental heart failure, has been partially attributed to increased protein phosphatase 1 (PP‐1) activity, associated with down‐regulation of its endogenous inhibitor‐1. The levels and activity of inhibitor‐1 are reduced in failing hearts, contributing to dephosphorylation and inactivation of key calcium cycling proteins. Therefore, we investigated the mechanisms that mediate decreases in inhibitor‐1 by post‐transcriptional modification. Methods and Results Bioinformatics revealed that 17 human microRNAs may serve as modulators of inhibitor‐1. However, real‐time PCR analysis identified only one of these microRNAs, miR‐765, as being increased in human failing hearts concomitant with decreased inhibitor‐1 levels. Expression of miR‐765 in HEK293 cells or mouse ventricular myocytes confirmed suppression of inhibitor‐1 levels through binding of this miR‐765 to the 3'‐untranslated region of inhibitor‐1 mRNA. To determine the functional significance of miR‐765 in Ca2+ cycling, pri‐miR‐765 as well as a non‐translated nucleotide sequence (miR‐Ctrl) were expressed in adult mouse ventricular myocytes. The inhibitor‐1 expression levels were decreased, accompanied by enhanced PP‐1 activity in the miR‐765 cardiomyocytes, and these reflected depressed contractile mechanics and Ca2+ transients, compared with the miR‐Ctrl group. The depressive effects were associated with decreases in the phosphorylation of phospholamban and SR Ca2+ load. These miR‐765 negative inotropic effects were abrogated in inhibitor‐1‐deficient cardiomyocytes, suggesting its apparent specificity for inhibitor‐1. Conclusions miR‐765 levels are increased in human failing hearts. Such increases may contribute to depressed cardiac function through reduced inhibitor‐1 expression and enhanced PP‐1 activity, associated with reduced SR Ca2+ load.